Bluetooth application developer's guide the short range interconnect solution - Kammer, David; McNutt, Gordon; Senese, Brian P.; Bray, Jennifer, 1964- (Rockland, Mass. : Syngress Pub., 2002)
"Bluetooth (enabled devices) will ship in the billions of units once it gains momentum."--Martin Reynolds, Gartner Group Bluetooth is the most exciting development in wireless computing this decade! Bluetooth enabled devices can include everything from network servers, laptop computers and PDAs, to stereos and home security systems. Most Bluetooth products to hit the market in 2001 will be PC cards for laptop computers and access points, which allow up to seven Bluetooth devices to connect to a network. Reports indicate that by the end of 2003 there will be over 2 billion Bluetooth-enabled devices. Bluetooth-enabled devices communicate with each other through embedded software applications. Bluetooth Developer's Guide to Embedded Applications will provide embedded applications developers with advanced tutorials and code listings written to the latest Bluetooth's latest specification, version 1.1. Written by Bluetooth pioneers from market leaders in Bluetooth software development, Extended Systems and Cambridge Silicon Radio, this is the first advanced level Bluetooth developer title on the market. White Hot Topic!. While other books introduce readers to the possibilities of Bluetooth, this is the first comprehensive, advanced level programming book written specifically for embedded application developers Authors are responsible for SDK, the market-leading development tool for Bluetooth Comes with Syngress' revolutionary Credit Card CD containing a printable HTML version of the book, all of the source code and sample applications from Extended Systems and Cambridge Silicon Radio.
Introducing Bluetooth applications -- Exploring the foundations of Bluetooth -- Power management -- Security management -- Service discovery -- Linux Bluetooth development -- Embedding Bluetooth applications -- Using the Palm OS for Bluetooth applications -- Designing an audio application -- Personal information base case study -- Bluetooth application developer's guide fast track.
Includes index.
Keywords: Bluetooth technology; Computer network protocols; Electronic books